Chinese women's attitudes towards postpartum interventions to prevent type 2 diabetes after gestational diabetes: a semi-structured qualitative study - Jie Shang; Amanda Henry; Puhong Zhang; Huan Chen; Kelly Thompson; Xiaodong Wang; Na Liu; Jiani Zhang; Yan Liu; Jianbo Jin; Xiongfei Pan; Xue Yang; et al. (BMC, 2021)
Plain language summary Gestational diabetes mellitus (GDM) is a common pregnancy complication affecting up to 1 in 6 pregnant women worldwide. Whilst the condition usually resolves soon after delivery, women are at high risk of developing type 2 diabetes mellitus (T2DM). In this study, we asked women living in Chengdu, a city in western China, about what they knew about their risk of diabetes and how they felt about participating in interventions after birth to prevent T2DM. After listening to the views of 20 women, we concluded that in this setting most women are happy to attend T2DM screening programs after birth, and would be willing to consider participating in interventions and research after birth to prevent T2DM. The interventions most preferred were those that aimed at lifestyle changes, and many women said would like to receive this information through their smartphone, for example through an app or social media channel. Women were reluctant to take medications to prevent T2DM. The main factors that influenced how women felt towards interventions to prevent T2DM were: (1) their experiences with the health system during pregnancy; (2) whether the home environment was supportive to make changes to diet and lifestyle; (3) any experiences of T2DM in family members; (4) their knowledge of diabetes and perception of risk; (5) concerns about personal and baby health; (6) feelings and emotions in the postnatal period, and (7) lifestyle constraints making it difficult to make dietary changes.